2014
DOI: 10.1186/1475-925x-13-82
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema early diagnosis using X-ray diffraction enhanced imaging at synchrotron light source

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is one of the leading causes of morbidity and mortality worldwide, and emphysema is a common component of COPD. Currently, it is very difficult to detect early stage emphysema using conventional radiographic imaging without contrast agents, because the change in X-ray attenuation is not detectable with absorption-based radiography. Compared with the absorption-based CT, phase contrast imaging has more advantages in soft tissue imaging, because of its high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In XPCI the USAXS signal has been shown to be useful in various applications such as, for example, the better visualization [26,27] and the quantification [28] of microbubbles used as contrast agents. Moreover, a dependence of the scattering signal on lung disease state was observed [17,29,30]. Recently, it has been reported that the scattering signal of EI, in combination with the absorption signal, and the dependence on the radiation energy can help distinguishing threat materials from benign materials in a security control [31].…”
Section: Introductionmentioning
confidence: 99%
“…In XPCI the USAXS signal has been shown to be useful in various applications such as, for example, the better visualization [26,27] and the quantification [28] of microbubbles used as contrast agents. Moreover, a dependence of the scattering signal on lung disease state was observed [17,29,30]. Recently, it has been reported that the scattering signal of EI, in combination with the absorption signal, and the dependence on the radiation energy can help distinguishing threat materials from benign materials in a security control [31].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary function tests measure the air inhaled and exhaled by the lungs, which is not just relevant to emphysema disease. 5 A chest x-ray is often performed to assess the overall condition of the lungs and identify any abnormalities, which can help diagnose advanced pulmonary emphysema, but is not sensitive to mild and moderate emphysema. 6 Traditional computed tomography scan of the chest provides more details of the lungs than chest x-rays, allowing one to assess the severity, extent, and distribution of emphysema.…”
Section: Introductionmentioning
confidence: 99%
“…Current existing methods typically involve pulmonary function tests, chest x‐rays, and computed tomography (CT) scans. Pulmonary function tests measure the air inhaled and exhaled by the lungs, which is not just relevant to emphysema disease 5 . A chest x‐ray is often performed to assess the overall condition of the lungs and identify any abnormalities, which can help diagnose advanced pulmonary emphysema, but is not sensitive to mild and moderate emphysema 6 .…”
Section: Introductionmentioning
confidence: 99%